Future mobility insights: a trend receiver approach - Beatrice Hügler; Birte Manke (Technium Social Sciences Journal, 2020)
The mobility sector is changing due to its negative consequences and companies’ reactions thereupon. New mobility solutions enter the market quickly, while it is uncertain where the shift in the industry will lead. Thus, companies ought to understand people’s future mobility needs to successfully adjust their innovations accordingly. This study examines customers’ insights into future mobility via trend receiver interviews in Europe, the United States and China. Findings reveal that some companies’ current strategies align with future customers’ mobility expectations, while other innovations may be under- or overestimated. These insights are of value for automobile manufacturers, marketing managers as well as for governments and city planners to positively influence the mobility future of mobility.